2011
DOI: 10.1080/10665684.2011.610682
|View full text |Cite
|
Sign up to set email alerts
|

Awakening Teachers’ Capacities for Social Justice With/In Arts-Based Inquiries

Abstract: Social justice-oriented teacher education can guide preservice teachers toward greater critical sociocultural knowledge, analytic skills, social responsibility, and commitment to act in the interest of providing all students with high quality educational experiences. This qualitative case study examines how arts-based inquiries in social justice-oriented teacher education can provide the necessary generative spaces for developing preservice teachers' critical sociocultural knowledge. Data were drawn from stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Art instructors and art instructional media default to teaching students how to draw White male characters, and encourage depictions of characters in stereotypical and gendered roles. Some art educators actively work against the spreading of negative stereotypical beliefs (Kraehe & Brown, 2011;Lee, 2012), but others fear backlash. In a study of preservice art teachers' attitudes about LGBTQ issues, Hsieh (2016) found that educators are "ready and willing to discuss sensitive LGBTQ issues with students.…”
Section: Culturally Conscious Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Art instructors and art instructional media default to teaching students how to draw White male characters, and encourage depictions of characters in stereotypical and gendered roles. Some art educators actively work against the spreading of negative stereotypical beliefs (Kraehe & Brown, 2011;Lee, 2012), but others fear backlash. In a study of preservice art teachers' attitudes about LGBTQ issues, Hsieh (2016) found that educators are "ready and willing to discuss sensitive LGBTQ issues with students.…”
Section: Culturally Conscious Contentmentioning
confidence: 99%
“…Fortunately, these practices are not limited to art instruction classrooms. Teachers of other subjects are also providing nonarts students opportunities to engage in similar educational experiences by incorporating artsbased inquiries into their assignments (Kraehe & Brown, 2011). Common arts-based inquiry assignments include "creating collages; drawing diagrams and depictions; writing fiction and nonfiction narratives; developing storyboards; and recording, acting, and editing a film" (Kraehe & Brown, 2011, p. 494).…”
Section: Degandmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance aesthetically connected well with audiences on issues related to social justice, equity, and youth issues such as suicide, body image, identity, love, etc. This process is interdependent upon the other two themes within instructional design in that meaning made through art is a reconceptualization, interactive, and reflexive practice of problem finding (Kraehe & Brown, 2011). The simultaneity in which students in RunDSM used problem-posing issues from both a historical and modern-day lens to create spoken word poetry, among other art forms, supported their cultural and social knowledge about the world.…”
Section: Instructional Designmentioning
confidence: 97%
“…Arts-based inquiry can lead to aesthetic experiences allowing others to construct meaning of one's self and the world (Kraehe & Brown, 2011). The focus of arts-based research analysis is to create insight by illuminating awareness to important social and cultural phenomenon for which the research can serve as "a heuristic [process] through which we deepen and make more complex our understanding of some aspect of the world" (Barone & Eisner, 2012, p. 3) The method of analysis in arts-based research does not follow a prescribed process but, instead, is interpretive, iterative, and creative.…”
Section: Data Analysis Processmentioning
confidence: 99%